IMPLEMENTASI KEGIATAN EKSTRAKURIKULER PRAMUKA DALAM MEMBENTUK KEDISIPLINAN KESETIAAN DAN KEBERANIAN SISWA KELAS 5 SD NEGERI 31 BANDA ACEH - Hafidh, Azza Al; Aswita, Dian; Julia, Putry (Jurnal Seramoe Education, 2025)
This research is based on problems regarding the implementation of scout extracurricular activities in forming discipline, loyalty and courage in students at SD Negeri 31 Banda Aceh. The approach in this research uses a qualitative approach with descriptive research type. The subjects in this research used a random sampling technique, meaning that all 25 class V students were the research subjects. The collection technique in this research is interview observation. The data analysis techniques in this research include data reduction, data presentation and drawing conclusions. The results of this research are from student observations and teacher interviews. The results of this research indicate that the implementation of scouting extracurricular activities as a means of increasing discipline, loyalty and courage in class V students has generally been implemented quite well. The instructor provides material to students, after presenting the material, students have the opportunity to apply it in practice. Scout extracurricular activities can improve loyalty discipline through marching drills, ceremonies, camping activities, scout skills competitions, group assignments and other activities. This can be seen from being disciplined in time, being loyal to your group of friends and being brave enough to take on new challenges and managing your time well at school and outside of school. Discipline in dress and dare to take risks and be loyal to the establishment. Discipline, Loyal, Courageous can create a comfortable and conducive learning environment.